From VR to ER in the Recovery of Artistic Heritage - Ramos-Fabra, Lidón; Pesqueira-Calvo, Carlos; Delgado-Ramos, Emilio; García-León, David (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The first contribution of the project is to evaluate the application of virtual reality (VR) in the recovery of artistic heritage. VR emerges as an innovative tool, transforming the interaction of viewers with artworks through computer-generated three-dimensional environments. This technology allows artists to develop interactive installations and immersive experiences, where users not only observe, but actively participate. The project has evolved towards the optimization of VR, extending its application from heritage recovery to the creation of new fully virtual works, with the potential to integrate artificial intelligence into future artistic experiences.